Symbolic Computational Models for Intuitionistic Linguistic Information - Phong, Phạm Hồng; Cường, Bùi Công (Journal of Computer Science and Cybernetics, 2016)
In Cuong14, Phong14, we first introduced the notion of intuitionistic linguistic labels. In this paper, we develop two symbolic computational models for intuitionistic linguistic labels (intuitionistic linguistic information). Various operators are proposed, their properties are also examined. Then, an application in group decision making using intuitionistic linguistic preference relations is discussed.